A Large Community Outbreak of Guillain–Barré Syndrome in Pune City, India, 2025 - Rajlakshmi Viswanathan; Pradnya Shinde; Mallika Lavania; Basavaraj Mathapati; Manohar L. Chaudhary; Gajanan N. Sapkal; Shailesh D. Pawar; Vijay P. Bondre; Anuradha S. Tripathy; Kavita S. Lole; Varsha A. Potdar; Pradip V. Barde; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Guillain–Barré syndrome (GBS) is a rare and potentially fatal immune-mediated disorder. During a large community outbreak in Pune City, India, investigations of GBS cases were conducted to identify the causes of antecedent or concurrent infections using serological and molecular methods. Water and poultry samples were also tested to determine the source of infection. From January to March 2025, 230 GBS cases, including 12 deaths (case fatality ratio 5.2%), were investigated. The cases were concentrated in Southwest Pune. All age groups were affected, with a male-to-female ratio of 2.2:1. Antecedent illness was reported in 147 (63.9%) cases, primarily diarrhea (37%). Among 193 cases, 108 (56%) were linked to infectious agents. Campylobacter jejuni ( C. jejuni ) infection was confirmed in 72 (48.7%) of 148 cases. Norovirus was confirmed in 40 (22.2%) of 180 cases, either as a coinfection ( n = 19) or alone ( n = 21). Water contamination was detected, with positive results for Campylobacter ( n = 1/208) and norovirus ( n = 8/208). Among 66 fecal samples from poultry, Campylobacter and norovirus were detected in 24 and five samples, respectively. No evidence of toxins was found in the nine water samples tested representatively. A significant GBS outbreak occurred in Pune City in early 2025, preceded by an acute diarrhea outbreak. A mixed etiology of the GBS outbreak was confirmed, with C. jejuni the leading cause in nearly half of the cases. Norovirus infection was also identified in more than one-fifth of the cases. Water contamination by both agents was detected, along with a possible link to poultry as a source of infection.